Effect of Cu(II) and Cr(VI) on oxidative stress actinomycete strains isolated from polluted area - Villegas, Liliana Beatriz (2007)
Heavy metals can induce the formation of reactive oxygen species in the cell due to its redox properties. These forms of oxygen damage the cellular constituents causing oxidative stress. However, these molecules are detoxified by superoxide dismutases (SOD) and catalases (CAT). The aim of this work was to study the Cu(II) or Cr(VI) effect on the SOD and CAT activities in two actinomycete strains. . ABO and . MC1, isolated from contaminated sediments by heavy metals. The microorganisms were incubated in Minimal Medium-glucose supplemented with 10 and 20 ppm Cu(II)/Cr(VI). SOD activity was detected at 24, 48 and 72 h of incubation for native polyacrylamide gel electrophoresis and activity staining. The catalase activity was measured spectrophotometricaly by absorption decreasing at 240nm. Cells incubated in the absence of heavy metals were used as control. Cu(II) and Cr(VI) concentrations enhanced the total SOD and CAT activities from both strains and they increased with incubation time. While . ABO presented two bands, . MC1 showed a single band with SOD activity. One of the band from ABO and the band from . MC1 were sensitive to H O ; thus, they correspond to FeZnSOD. The second band from . ABO were not inhibited neither with nor N N , corresponding to MnSOD.